2018
DOI: 10.1017/dmp.2018.66
|View full text |Cite
|
Sign up to set email alerts
|

Incidents That Require First Aid in Schools: Can Teachers Give First Aid?

Abstract: Understanding the causes of accidents and injuries, finding preventive measures, and updating teachers' knowledge about this subject are important to provide a safe educational environment. (Disaster Med Public Health Preparedness. 2018;page 1 of 7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
1
9
0
15
Order By: Relevance
“…5 Regarding practice component; 21.6% of the teachers answered correctly about the management of epistaxis, these findings were lower (66.4%) 13 than the study conducted in Palestine 13 in 2017 and comparable with the study conducted in Egypt where (18%) 14 cases of epistaxis were given correct first aid.In this study 38.9% of the participants answered correctly about the management of bleeding wound,in another study done in India showed that 80.8% people had correctly practiced first aid for bleeding wound. 15 In this study 29.0% of the teachers correctly answered about the management of a child who faints suddenly and this is comparable with the other studies stated that 18.4% people give correct answers about management of loss of conscious, 11 15.8% cases were correctly managed, 2 respectively. Total 46.9% of teachers answered correctly about the first aid management of limb fracture in our study and this is inconsistent with the another study which stated that 10.5% of school teachers answered correctly.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…5 Regarding practice component; 21.6% of the teachers answered correctly about the management of epistaxis, these findings were lower (66.4%) 13 than the study conducted in Palestine 13 in 2017 and comparable with the study conducted in Egypt where (18%) 14 cases of epistaxis were given correct first aid.In this study 38.9% of the participants answered correctly about the management of bleeding wound,in another study done in India showed that 80.8% people had correctly practiced first aid for bleeding wound. 15 In this study 29.0% of the teachers correctly answered about the management of a child who faints suddenly and this is comparable with the other studies stated that 18.4% people give correct answers about management of loss of conscious, 11 15.8% cases were correctly managed, 2 respectively. Total 46.9% of teachers answered correctly about the first aid management of limb fracture in our study and this is inconsistent with the another study which stated that 10.5% of school teachers answered correctly.…”
Section: Discussionsupporting
confidence: 77%
“…16 Our study showed that 29.6% of teachers knew the correct first aid of treating bee/wasp bite and these results are better than the study of Fiaydali 2018; which showed that 10.3% of participants answered correctly. 11 Majority of participants (54.9%) knew the correct first aid of electrical burn, while other study in Turkey showed that only 1.8% cases were correctly given first aid of electric burn. 11 In this study, 59.3% of teachers answered correctly about managing the child with a chemical burn, while another study of China showed only 23.05% of participants know the correct first aid.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Os acidentes são eventos inesperados que levam a danos corporais ou psicológicos que ocorrem repentinamente fora da vontade humana, e são considerados um problema de saúde global, além da principal causa de morte em crianças em quase todos os países (FAYDALI; KÜÇÜKE; YEŞILYURT, 2018; Revista Docent Discunt, Engenheiro Coelho, SP, volume 02, número 2, p. 14-27, 2º semestre de 2021 https://doi.org/10.19141/2763-5163.docentdiscunt.v2.n2.p14-27 Centro Universitário Adventista de São Paulo -Unasp Revista Docent Discunt Primeiros socorros para profissionais da educação infantil: um estudo quase-experimental 16 BARCELOS; DEL-PONTE; SANTOS, 2018). E, de modo geral, a literatura aborda a temática por expressões como "unintentional childhood injuries" (lesões não intencionais na infância) e "childhood accidents" (acidentes infantis), no ambiente escolar (school accidents), familiar e comunidade (WHO, 2021;TUPETZ et al, 2020;RIBEIRO et al, 2019;ZONFRILLO et al, 2018;FAYDALI;KÜÇÜKE;YEŞILYURT, 2018).…”
unclassified
“…A lesões não fatais também causam um enorme fardo socioeconômico, já que no mundo, anualmente, quase uma em cada quatro crianças é ferida com gravidade suficiente para exigir atenção médica, resultando em U$ 17 bilhões em custos médicos (LI et al, 2014). Estima-se ainda que de 10% a 25% das lesões acidentais em crianças com idade igual ou inferior a 14 anos ocorrem em escolas ou perto delas (ALYAHYA et al, 2019;FAYDALI;KÜÇÜKE;YEŞILYURT, 2018).…”
unclassified